THE APPLICATION OF THE FINANCIAL REPORTING STANDARD IFRS-13 AND ITS IMPACT ON THE POLICY OF DIVIDEND DISTRIBUTION AND TRADING VOLUME (APPLIED STUDY IN THE MIDDLE EAST INVESTMENT BANK) (World Economics and Finance Bulletin, 2022)
The research aims to show the impact that accounting measurement and disclosure can play according to the principle of fair value under the IFRS-13 Financial Reporting Standard on the policy of profit distribution and trading volume in a way that conforms to the requirements of the contemporary business environment. The research has been applied in the Middle East Investment Bank for the years (2018-2021). Where the cash dividend model was used for the purpose of measuring the fair value in this bank. The research reached a set of conclusions, the most important of which was that there is a possibility to measure the fair value within the cash dividend discount models, the most appropriate model for the Iraqi environment at the present time, for the ease of application of the model, as well as the possibility of obtaining model variables through the final statements of companies in a way that can help improve The policy of distributing profits and trading volume in a way that is consistent with the various environmental changes
Keywords: environmental; distributing; Financial Reporting Standard; requirements